Factors influencing the participation of surrogate decision-makers for advanced cancer patients in advance care planning: A cross-sectional study - Zhihao Han; Jingjing Su; Guiyue Ma; Yong Fang; Linxia Tang; Xiaoqin Ma (PLoS ONE, 2025)
Aim The aim of this study was to explore the factors influencing surrogate decision-makers (SDMs) engagement in Advance Care Planning (ACP). Design A cross-sectional Study. Method A total of 285 SDMs of advanced cancer patients were recruited using convenience sampling methods. All eligible participants completed the structured questionnaires. Univariate and correlation analyses were used to explore the relationship between different variables and the ACP engagement of SDMs. Factors significant previously in univariate or correlation analyses were included in the multiple linear regression analyses with P < 0.05. Results Eight factors in univariate analyses and three factors in correlation analyses with P < 0.05 were taken into multiple linear regression analyses. Finally, seven variables revealed a statistically significant association with ACP engagement of SDMs and were included in the multiple linear regression model. Conclusion This cross-sectional study demonstrated that multiple factors, including experiences of medical decision-making, education level, knowledge of ACP, treatment expenditure, uncertainty of disease, social support, and life orientation, significantly impacted the engagement of SDMs in ACP. Impact Based on this study, we have identified some factors influencing the ACP engagement of SDMs, which might provide basic information for construction of the educational scheme of ACP in mainland China and help to improve SDMs’ engagement in clinical ACP practice in the future. Patient or public contribution SDMs of advanced cancer patients participated in this study, and assisted in assessing the validation of the measurements.